Methodological Proposal for the Adaptation of the Living with Long-Term Conditions Scale to the Family Caregiver - Patricia Marín-Maicas; Mari Carmen Portillo; Silvia Corchón; Leire Ambrosio (MDPI AG, 2024)
(1) Background: Living with long-term conditions affects both patients and family caregivers. To obtain a more complete overview of this phenomenon, a measurement instrument is needed that includes both perspectives. The aim is to adapt a scale to family caregivers of individuals with long-term conditions. (2) Methods: A methodological proposal is presented that illustrates the adaptation of the EC-PC scale to the family caregiver. Three phases are proposed: adaptation of the items, panel of experts, and pre-test. (3) Results: In the adaptation phase, the items from the original EC-PC were modified to adapt them to the family caregiver, and new items were added associated with the differences in living with LTC from the perspective of family caregivers. In the panel of experts phase, a universal agreement was reached related to the clarity, relevance, and essentiality of the items included. In the pre-test phase, the content of the scale was verified quantitatively and qualitatively. (4) Conclusions: The content of the items of version 5 of the EC-PC-Family showed a high index of inter-judge agreement. When a phenomenon affects both patients and their environment, such as living with LTC, it is necessary to include both perspectives in the measurement tools.